Gender differences in loss of sexual activity 1-year after an acute myocardial infarction (AMI) - Lindau, S.; Gosch, K.; Abramsohn, E.; Chan, P.; Krumholz, H.; Spatz, E.; Wroblewski, K.; Spertus, J. (Circulation: Cardiovascular Quality and Outcomes, 2011)
Objectives: Little is known about sexual activity after an AMI and the extent to which physicians discuss this with their patients. We compared sexual activity, predictors of change in activity, and patterns of communication with physicians about sexual activity among men and women following an AMI. Methods: Between 2005-08, the TRIUMPH Study enrolled 4340 AMI patients and surveyed them at baseline, 1, 6, and 12 months. In 9/07, a sexual health module to assess pre- and post-MI sexual activity and communication was added and administered at months 1 and 12; a total of 1184 men and 576 women received the module at their one year follow-up. Multivariable hierarchical models (separate for men and women), within site, were used to predict loss of sexual activity 1 year after an AMI. Loss of sexual activity was defined as less frequent or no sexual activity in those who were sexually active prior to an MI. Item non-response for the sexuality module ranged from 4.4%-5.9%. Findings: Participants were 58.6 ± 11.0 years (males) and 61.0 ± 12.9 years (females) old. Women were less likely than men to be married (40.6% of 574 vs 64.6% of 1182, p<0.001), and less likely to be sexually active prior to the MI (43.1% of 504 vs 73.5% of 1095, p<0.001). At 1 year, men were more likely than women to report having received discharge instructions about resuming sexual activity (46.3% of 1163 and 34.5% of 556, p<0.001, respectively). Men were more than twice as likely as women to report having discussed sex with a physician in the year following MI (38.8% of 896 vs 17.5% of 325, p<0.001). The majority of men (67.7% of 1100) but less than half of women (40.6% of 505) reported some sexual activity in the year following an MI. Controlling for age, partner status, GRACE 6-month mortality risk score, depression (PHQ-9), and physical health (SF-12) (all at baseline), those who did not receive discharge instructions about sexual activity were significantly more likely to report loss of sexual activity at one year (RR 1.32, 1.14-1.54 for men and RR 1.41, 1.16-1.72 for women). Conclusions: Discussion with a physician about sex occurs much less often for women than men. Lack of physician-patient communication about sex prior to hospital discharge after an MI is independently associated with loss of sexual activity at one year.
Keywords: acute heart infarction; cardiovascular disease; cerebrovascular accident; female; follow up; health; heart infarction; hospital discharge; human; interpersonal communication; male; married person; model; mortality; outcomes research; patient; patient care; physician; sex difference; sexual behavior; sexual dysfunction; sexual health; sexuality